Dynamic change of soil aggregate stability and infiltration properties during crop growth under four tillage measures in Mollisols region of northeast China - Xu, Chong; Liu, Wenli; Li, Jianming; Wu, Jinggui; Zhou, Yinuo; kader, Rehanguli (Frontiers in Earth Science, 2024)
Previous studies have proven that different tillage measures have significant different effects on soil structure, hydrology properties and soil erosion. However, few studies have clarified the dynamic changes in soil aggregate stability and infiltration properties during crop growth under four tillage measures. Four field plots (150 m × 15 m) managed by four tillage methods including wide ridge tillage (DT), no-tillage (NT), contour ridge tillage (CT) and traditional tillage (CK) were built in 2021 to evaluate their effects on dynamic changes of soil structure and water conductivity during crop growth. Soybean was the seasonal crop. Soil bulk density, soil porosity, soil aggregate stability and soil infiltration characteristics were measured to assess dynamic changes in soil aggregate stability and infiltration from June to October 2022. The results showed that NT significantly increased soil bulk density by up to 21.62% compared with CK, while DT did not show significantly increase in soil bulk density. DT, NT and CT could greatly increase the capillary porosity and proportion of capillary porosity to total porosity. DT and NT also improved the stability of soil water-stable aggregates by 3.37% and 10.6%. In terms of soil infiltration properties, all three tillage methods increased the initial, stable and average infiltration rates by 8.4%-52.94%, of which the DT and NT showed the greatest improvement. The soil infiltration process of four tillage measures could be better fitted by Horton model than Kostiakov and Philip models. Soil saturated hydraulic conductivity (SHC) of CK exhibited a significant negative correlation with soil bulk density and capillary porosity, and showed a positive correlation with total porosity and geometric average diameter of water-stable aggregate (GMD), whereas the other three treatments only displayed a significant correlation with the stability of soil water-stable aggregate. The results suggest that DT, NT and CT have potential to improve soil structure and infiltration capacity compared with CK, and contribute to preventing and controlling soil erosion in sloping farmland of Northeast China.